Faktor-faktor yang berhubungan dengan kepatuhan orang tua dalam membawa penderita talasemia untuk menjalani transfusi darah selama pandemi covid - Antika Palupi; Djunizar Djamaludin; Linawati Novikasari; Setiawati setiawati (Holistik Jurnal Kesehatan, 2023)
Background: Blood transfusion in the mainstay of management for someone with thalassemia major and intermedia. One of the hospitals that provide excellent service facilities in the thalassemia section of children in the province of Lampung is Regional Public Hospital Dr H Abdul Moeloek in the Alamanda room. In 2020 it decreased to 110 patients/month. And in 2021 there are 104 patients every month who are registered for blood transfusions.Purpose: To determine the factors related to parental compliance in bringing thalassemia patients to undergo blood transfusions during the Covid pandemic in the alamanda room of Regional Public Hospital Dr H Abdul Moeloek Lampung Province in 2022.Method: Quantitative with a cross sectional design. The study population was thalassemia pediatric patients who received blood transfusion therapy who were being treated in the Alamanda room of Regional Public Hospital Dr H Abdul Moeloek Lampung Province. In December the number of patients treated was 83 patients. The sample is 52 respondents. The statistical test used the chi square test.Results: Frequency distribution of respondents aged <45 years (59,6 percent), female (63,5 percent), low education (59,6 percent), not working (57,7 percent), living outside Bandar Lampung (59,6 percent), had poor knowledge about thalassemia (75 percent), did not comply with bringing thalassemia sufferers to undergo blood transfusions during the Covid pandemic (59,6 percent).Conclusion: There is a relationship between parental age, gender parental education, occupation, place of residence and parental knowledge relationship with parental compliance in bringing thallasemia sufferers to undergo blood transfusions during the Covid pandemic. Keywords: Compliance; Transfusion; Thalassemia; Pandemic.Pendahuluan: Transfusi darah merupakan penatalaksanaan andalan bagi seseorang dengan talasemia mayor dan intermedia. Salah satu Rumah Sakit yang menyediakan fasilitas unggulan layanan dibagian talasemia anak di Provinsi Lampung yaitu RSUD Dr. H. Abdul Moeloek di ruang alamanda. Di tahun 2020 menurun menjadi 110 pasien/bulan. Dan di tahun 2021 terdapat 104 pasien setiap bulannya yang teregistrasi untuk melakukan tranfusi darah.Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kepatuhan orang tua dalam membawa penderita talasemia untuk menjalani tranfusi darah selama pandemi covid diruang alamanda RSUD Dr H Abdul Moeloek Provinsi Lampung Tahun 2022.Metode: Kuantitatif dengan rancangan cross sectional. Populasi penelitian adalah pasien anak thalassemia yang mendapatkan terapi transfusi darah yang sedang dirawat di ruang alamanda RSUD Dr H Abdul Moeloek Provinsi Lampung. Pada bulan Desember jumlah pasien yang dirawat 83 pasien. Sampel 52 responden. Uji statistik yang digunakan adalah uji chi square.Hasil: Distribusi frekuensi responden berusia < 45 tahun (59,6 persen), berjenis kelamin perempuan (63,5 persen), berpendidikan rendah (59,6 persen), tidak bekerja (57,7 persen), bertempat tinggal di luar Bandar Lampung (59,6 persen), memiliki pengetahuan bueruk tentang talasemia (75 persen), tidak patuh membawa penderita talasemia untuk menjalani tranfusi darah selama pandemi Covid (59,6 persen).Simpulan: Ada hubungan usia orang tua, jenis kelamin, pendidikan orang tua, pekerjaan, tempat tinggal dan pengetahuan orang tua dengan kepatuhan orang tua dalam membawa penderita talasemia untuk menjalani tranfusi darah selama pandemi Covid.